Potensi Ekonomi Lokal Dalam Pengembangan Daerah (Studi pada Kabupaten Serang) - Gusti, Muhammad Naufal (Jurnal Administrasi Publik, 2016)
Abstract: Local Economic Potency In Regional Development  (Study In Serang Regency). One of aspect that given by central government to local government to manage is regional economic development. If economic development in one region doesn’t appropriate with it’s potency, therefore will resulting in the slow process of economic growth in the region. The purpose of this study is to determine what are the excellent economic sectors in Serang Regency and whether the excellent economic sector has been developed in appropriate with proportions. The type of research used in this research is descriptive research with quantitative approach. The method of analysis in this research uses location quotient (LQ), shift share and sectoral typology for determine excellent economic sectors in the Serang Regency. The result of this research shows that there are three excellent economic sectors in Serang Regency. Those sector are, electricity, gas and water supply sector, the processing industry sector and the agricultural sector. In the overall, The Government of Serang Regency efforts in developing the excellent economic sector based on Regional Long Term Development Plan and Regional Medium Term Development Plan is already good enough because The Government of Serang Regency has given priority to the third excellent economic sector. However, viewed from Government Budget, Government of Serang Regency allocates only a little budget to the excellent economic sectors Keywords: Regional Economy Development, Regional Economy Potency, Location Quotient, Shift Share   Abstrak: Potensi Ekonomi Lokal Dalam Pengembangan Daerah (Studi Pada Kabupaten Serang). Salah satu aspek yang diberikan oleh pemerintah pusat kepada pemerintah daerah untuk dikelola adalah mengenai pembangunan ekonomi daerah. Apabila pembangunan ekonomi di suatu daerah tidak sesuai dengan potensi daerah tersebut, maka pertumbuhan ekonomi daerah tersebut menjadi lambat. Penelitian ini bertujuan untuk mengetahui sektor ekonomi apa sajakah yang menjadi sektor ekonomi unggulan di Kabupaten Serang dan apakah sektor ekonomi unggulan tersebut sudah dikembangkan sesuai dengan proporsinya. Jenis penelitian yang digunakan dalam penelitian ini adalah jenis penelitian deskriptif dengan pendekatan kuantitatif. Penelitian ini menggunakan metode location quotient (LQ), shift share dan tipologi sektoral. Hasil penelitian ini menunjukan bahwa terdapat tiga sektor ekonomi unggulan di Kabupaten Serang, yakni sektor listrik, gas dan air bersih, sektor industri pengolahan dan sektor pertanian. Secara keseluruhan upaya pemerintah Kabupaten Serang dalam mengembangkan sektor ekonomi unggulannya yang dilihat dari RPJPD dan RPJMD sudah cukup baik karena Pemerintah Kabupaten Serang sudah memberikan prioritas pengembangan kepada ketiga sektor ekonomi unggulan tersebut. Namun jika dilihat dari alokasi APBD, Pemerintah Kabupaten Serang hanya mengalokasikan sedikit anggaran belanja kepada sektor-sektor ekonomi unggulan. Kata kunci: Pembangunan Ekonomi Daerah, Potensi Ekonomi Lokal, Location Quotient, Shift Share